Imunologické aspekty v onkologii--cirkulující γδ T lymfocyty - Cibulka, M; Selingerová, I; Fědorová, L; Zdražilová Dubská, L (Klinicka onkologie, 2015)
γδ T cells present a minor population of the T cell family which basically differs in construction of their T cell receptor (TCR). Thanks to the features of γδ TCR, these cells can acquire unique effector functions and play a specific role (not only) in antitumor immune response. In this article, we describe the basic characteristics of this cell population and their connection to cancer. In the experimental part we performed exploratory analysis of circulating γδ T cells in reference population and comparison with melanoma and breast carcinoma patients. The median percentage of γδ T cells from all lymphocytes was 2.9% (interquartile range-IQR 1.7-4%). The median absolute numbers of γδ cells per liter of blood was 5.05×10(7) (IQR 2.9-7.84×10(7)). The median percentage of γδ cells between all CD3 T cells was 3.9% (IQR 2.3-5.6%). No correlation between γδ T cells levels and gender or age was observed in reference population. Detailed immunophenotyping was also conducted describing representation of memory subsets (using CD45RO and CD27 markers) and presence of surface markers HLADr, CD69, CD25, CD28, CCR7, CTLA 4, ICOS, PD 1L and PD 1 between γδ T cells of the controls and breast carcinoma patients. From this analysis, it is evident that γδ T cells do not represent a uniform population but they differ in surface markers as well as in their effector functions.
Keywords: Immunophenotyping; Neoplasms; Receptors, Antigen, T-Cell, gamma-delta; nádory; Animals; Humans; lidé; imunofenotypizace; T-Lymphocytes; zvířata; receptory antigenů T-buněk gama-delta; T-lymfocyty